2008
DOI: 10.4028/www.scientific.net/msf.600-603.147
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ</i> Boron and Aluminum Doping and Their Memory Effects in 4H-SiC Homoepitaxial Layers Grown by Hot-Wall LPCVD

Abstract: The in-situ p-type doping of 4H-SiC grown on off-oriented (0001) 4H-SiC substrates was performed with trimethylaluminum (TMA) and/or diborane (B2H6) as the dopants. The incorporations of Al and B atoms and their memory effects and the electrical properties of p-type 4H-SiC epilayers were characterized by secondary ion mass spectroscopy (SIMS) and Hall effect measurements, respectively. Both Al- and B-doped 4H-SiC epilayers were p-type conduction. It was shown that the profiles of the incorporated boron and alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Previous report on the memory effect of aluminum and boron doping in the chloride-based process at 2000 1C found a lowest achievable Al and B doping of 1 Â10 15 cm À3 and 2 Â 10 16 cm À3 , respectively, after growth of thick heavily p-type-doped epilayers [21]. Recent report on boron-and aluminum-doped layers grown in low pressure CVD (40 Torr) found a longer memory effect for aluminum than for boron [27]. It has previously been suggested that HCl-etch of the susceptor after growth reduces the memory effect of both aluminum and boron [12], however in [21] it is stated that the chlorine present in the process does not reduce the aluminum and boron content in unintentionally doped layers to the level before the growth of heavily doped layers.…”
Section: Memory Effectmentioning
confidence: 96%
“…Previous report on the memory effect of aluminum and boron doping in the chloride-based process at 2000 1C found a lowest achievable Al and B doping of 1 Â10 15 cm À3 and 2 Â 10 16 cm À3 , respectively, after growth of thick heavily p-type-doped epilayers [21]. Recent report on boron-and aluminum-doped layers grown in low pressure CVD (40 Torr) found a longer memory effect for aluminum than for boron [27]. It has previously been suggested that HCl-etch of the susceptor after growth reduces the memory effect of both aluminum and boron [12], however in [21] it is stated that the chlorine present in the process does not reduce the aluminum and boron content in unintentionally doped layers to the level before the growth of heavily doped layers.…”
Section: Memory Effectmentioning
confidence: 96%
“…Much research effort has been made to suppress the Al memory effect. [7][8][9][10][11] We have studied the suppression methods using site-competition growth and achieved a reduction factor (the ratio of Al concentration N Al in the undoped epilayer to that in the p + layer) of about 1/17,000, e.g., N Al from 9 © 10 19 to 6 © 10 15 cm ¹3 or from 1.7 © 10 20 to 1.0 © 10 16 cm ¹3 . 7) On the other hand, La Via et al reported that the growth using trichlorosilane can decrease the Al impurity level to 10 14 cm ¹3 after a p + epilayer growth with N Al ³ 1 © 10 18 cm ¹3 , but it is a concern that there may be an upper limit of Al doping level of approximately 10 18 cm ¹3 .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, only seldom works have been reported about Al memory-effect in CVD growth of SiC. 3,[5][6][7] One conclusive solution has been made that the growth should be carried out in separate reactors for n/p layers. 6) It is inapplicable in consideration of possible Al contaminations to n-reactor.…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7] One conclusive solution has been made that the growth should be carried out in separate reactors for n/p layers. 6) It is inapplicable in consideration of possible Al contaminations to n-reactor. Besides, a previous report demonstrates that the device by a continual growth shows superior performance than that grown by an interrupted growth.…”
Section: Introductionmentioning
confidence: 99%